We are to prove sum(n)(I=1)(k(I))*(x(I)) = 1(adsbygoogle = window.adsbygoogle || []).push({});

Where (k(I))= (x(I)-x(bar))/(sum(n)(j=1)(x(j)-x(bar))^2

Attempt at solution:

I rearranged it to equal:

(1/(sum(n)(j=1)(x(j)-x(bar))^2))*(sum(n)(I=1)(x(I)-x(bar))*x(I))

I don't really know how to proceed. Sorry for the formatting issues, I am on mobile currently.

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Stats proof - unbiasedness of b1

**Physics Forums | Science Articles, Homework Help, Discussion**